1984
DOI: 10.1093/carcin/5.12.1557
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 1-nitro[14C]pyrene in vivo in the rat and mutagenicity of urinary metabolites

Abstract: The metabolic fate of the bacterial mutagen, environmental pollutant and potential carcinogen 1-nitropyrene (NP) has been investigated in the rat. Over half of an i.p. dose (10 mg/kg) of 1-nitro[14C]pyrene was excreted within 24 h of dosing, 15% of the dose in urine and 40% in the faeces. After 96 h greater than 80% of the dose had been recovered. The urinary and fecal metabolites of NP were separated and quantitated by h.p.l.c., then identified by high resolution gas chromatography/mass spectrometry (h.r.g.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…This may be because some of the subjects had extremely low concentrations of urinary OHNAAPs. In studies with rats, ring hydroxylation in the liver seems to be the predominant route of 1-NP biotransformation, whereas nitroreduction occurs only to a small extent in the liver (17). Biotransformation by nitroreduction occurs mainly by intestinal bacteria (18,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because some of the subjects had extremely low concentrations of urinary OHNAAPs. In studies with rats, ring hydroxylation in the liver seems to be the predominant route of 1-NP biotransformation, whereas nitroreduction occurs only to a small extent in the liver (17). Biotransformation by nitroreduction occurs mainly by intestinal bacteria (18,45).…”
Section: Discussionmentioning
confidence: 99%
“…1-NAAP was prepared by acetylation of 1-AP with acetic anhydride in ethyl acetate. To identify the synthesized compounds, their GC-MS and proton NMR spectra were compared with data in the literature (17,34,35). Similar procedures were applied to synthesize deuterated OHNPs and OHNAAPs from pyrene-d 10 for use as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…1) in the presence of cytochrome P450 enzymes. 3,4) Additionally, OHNPs were observed in airborne particles 5,6) and diesel exhaust particles. 7,8) The mutagenicity of OHNPs has been investigated by several groups, and they concluded that most of OHNP isomers showed lower activity than the parent 1-NP.…”
Section: Introductionmentioning
confidence: 99%
“…1), such as 1-hydroxy-3-nitropyrene (1-OH-3-NP), 1-hydroxy-6-nitropyrene (1-OH-6-NP), and 1-hydroxy-8-nitropyrene (1-OH-8-NP) in the presence of cytochrome P450 enzymes. 4,5) We recently found that these OHNP isomers were also produced from a photoreaction of 1-NP in the atmosphere as well as the other isomers, 1-hydroxy-2-nitropyrene (1-OH-2-NP) and 1-hydroxy-5-nitropyrene (1-OH-5-NP). 6) Several groups reported that 1-OH-3-NP, 1-OH-6-NP, and 1-OH-8-NP are weakly muta- The Pharmaceutical Society of Japan genic, [7][8][9][10] but the mutagenicities of 1-OH-2-NP and 1-OH-5-NP are unknown.…”
Section: Introductionmentioning
confidence: 99%